Cover Image. (12th May 2018) - Yurt, Fatma; Ersöz, Onur Alp; Harputlu, Ersan; Ocakoglu, Kasim
Abstract : The cover image, by Fatma Yurt et al ., is based on the Research Article Preparation and evaluation of effect on E. coli and S. aureus of radiolabeled Ampicillin loaded graphene oxide nanoflakes, DOI:10.1111/cbdd.13171 .